Urban-rural variation in the association between social support availability and cognitive function in middle-aged and older adults: Results from the baseline Tracking Cohort of the Canadian Longitudinal Study on Aging. (September 2022) - Quick, Matthew; Rutter, Emily; Tyas, Suzanne L.; Maxwell, Colleen; Law, Jane; Oremus, Mark
Abstract: The purpose of this study was to investigate if and how the associations between social support availability (SSA ) and cognitive function varied across urban, rural, and geographical regions in Canada. Data from a population-level sample of community-dwelling adults aged 45–85 years were obtained from the baseline Tracking Cohort of the Canadian Longitudinal Study on Aging. The associations between SSA and two domains of cognitive function, memory and executive function, were analyzed using multilevel regression models. SSA was positively and significantly associated with both executive function and memory. We found SSA had stronger positive associations with executive function among participants living in rural areas compared to urban areas in all geographical regions; however, geographical variation in the associations between SSA and memory were not supported by model results. Understanding how the associations between cognitive function and modifiable risk factors, including SSA, vary across geographical contexts is important for developing policies and programs to support healthy aging. Highlights: Social support availability (SSA) was positively associated with cognitive function. SSA had stronger associations with executive function in rural compared to urban areas. Consistent urban-rural variations in the association between SSA and executive function were found in all regions. Urban-rural and regional variations were not observed for the association between SSA and memory.